Isolation of a psaF-deficient mutant of Chlamydomonas reinhardtii: efficient interaction of plastocyanin with the photosystem I reaction center is mediated by the PsaF subunit. - Farah, J (1995)
The PsaF polypeptide of photosystem I (PSI) is located on the lumen side of the thylakoid membrane and its precise role is not yet fully understood. Here we describe the isolation of a psaF-deficient mutant of the green alga Chlamydomonas reinhardtii generated by co-transforming the nuclear genome of the cw15-arg7A strain with two plasmids: one harboring a mutated version of the psaF gene and the other containing the argininosuccinate lyase gene conferring arginine prototrophy. This psaF mutant still assembles a functional PSI complex and is capable of photoautotrophic growth. However, electron transfer from plastocyanin to P700+, the oxidized reaction center chlorophyll dimer, is dramatically reduced in the mutant, indicating that the PsaF subunit plays an important role in docking plastocyanin to the PSI complex. These results contrast with those obtained previously with a cyanobacterial psaF-, psaJ- double mutant where no phenotype was apparent.